1981
DOI: 10.7164/antibiotics.34.576
|View full text |Cite
|
Sign up to set email alerts
|

An active intermediate formed in the reaction of bleomycin-Fe(II) complex with oxygen.

Abstract: The base-release activity of oxygen adduct of bleomycin-Fe(ll) complex ] from DNA decreased with a half-life of 5.2 minutes, when incubated at 0°C in 0.05 M Tris-HCl buffer at pH 7.8 in the absence of DNA. Under the same condition, however, visible and ESR spectra showed that the adduct was immediately converted into the ferric complex. The ESR study further indicated the simultaneous formation of two kinds of the low-spin BLM-Fe(III) complex. One of them disappeared in parallel with the decrease of the base-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
76
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(77 citation statements)
references
References 18 publications
1
76
0
Order By: Relevance
“…Experiments in animals also showed that exposure to air having an elevated concentration of oxygen increased the development of BLM-induced fibrosis (25), while hypoxia decreased it (26). In addition, it is reported (27) that the cytotoxicity of BLM is due to DNA breakage caused by the generation of superoxide free radicals in the presence of iron (II). As we have reported (8), however, tranilast does not suppress the tumorcidal activity of BLM in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments in animals also showed that exposure to air having an elevated concentration of oxygen increased the development of BLM-induced fibrosis (25), while hypoxia decreased it (26). In addition, it is reported (27) that the cytotoxicity of BLM is due to DNA breakage caused by the generation of superoxide free radicals in the presence of iron (II). As we have reported (8), however, tranilast does not suppress the tumorcidal activity of BLM in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…A possible question is whether this situation could also occur for the antitumour antibiotics which bear a quinone-type moiety [l, 3,4,8,91. In order to answer this question, we performed quantum-mechanical computations (Materials and Methods) using two models displayed in Fig.…”
Section: S-mentioning
confidence: 99%
“…Some provoke strand breakage of DNA as one aspect of their mechanism of action. These include bleomycin [3,41, streptonigrin [5], mitomycin C [6], neocarzinostatin [7] and the anthracyclines [S, 91. Although there are several differcnces in structure and the exact mechanism of action, all appear to form radical species.…”
mentioning
confidence: 99%
“…ABLM is proposed to be a low spin (ls) Fe III ─OOH species (9)(10)(11), that can be formed via the reaction of Fe III BLM with O 2 and an electron or through a shunt reaction between Fe III BLM and H 2 O 2 (8,12).…”
mentioning
confidence: 99%